Mapping Linkages between Actors in Cattle Marketing Innovation System of Northeastern Nigeria - Altine Madugu (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The focus of this study was to analyze and map linkages among actors in the innovation system of cattle marketing in northeastern Nigeria. Specifically, linkages/interactions between actors and those of the innovation system network were determined. A structured questionnaire was used to collect data from 48 respondents and a Focus Group Discussion (FGD) session involving sixteen (16) participants each was conducted in three out of the four Adamawa Agricultural Development Project (AADP) zones of Adamawa State. Analytical tools used were descriptive statistics such as means, tables, and charts while the inferential statistical tool used was the Social Network Analysis (SNA). The results of the FGD interaction sessions revealed that the sixteen (16) actors had ninety-nine (99) ties in the network; these were classified into nine (9) key and seven (7) non-key actors with each group performing specific roles in the system. Furthermore, the result of the social network analysis revealed a network density of 0.83, indicating that 83% of all direct linkages were present. However, the network cohesion was 0.40, showing that only 40.0% of the connections were reciprocated, which implied that about 40% of the actors are not well connected. The result further revealed that both extension agents/Village Based Agents and the cattle dealers association had the highest degree and closeness centrality (73% and 6 links each), implying that they are the actors with more connections, closest to others and thus directly able to influence the decisions of other actors in the network; they can also be considered as the most important channels/agents for the diffusion of innovations in the system. The result of the network diagram revealed that there were strong, weak, unidirectional and reciprocal links among actors in the system. A strong link signifies high/dense interaction while a weak link signifies low/loose interaction among actors. Furthermore, unidirectional links indicate a one-way interaction/communication process while a reciprocal link signifies a feedback communication process.